Multiple Evanescent White Dot Syndrome (MEWDS) Associated with Progression of Lacquer Cracks in High Myopia - Ong, Ariel Yuhan; Birtel, Johannes; Charbel Issa, Peter (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To report a case of multiple evanescent white dot syndrome (MEWDS) associated with acute progression of lacquer cracks in high myopia.Case Report A 41-year-old female patient with high myopia developed typical signs, symptoms, and disease course of MEWDS in her right eye. At the same time, the same eye showed progression of lacquer cracks when compared to images taken 2 months prior. Retinal imaging findings characteristic of MEWDS were most obvious on fundus autofluorescence, whereas alterations on color fundus photography, optical coherence tomography, fluorescein, and indocyanine green angiography were very mild, probably because of the myopia-related fundus pathology.Conclusion We present a case of MEWDS co-occurring with acute progression of lacquer cracks. This adds to the increasing evidence that impaired integrity of the retinal pigment epithelium-Bruchʼs membrane complex may be a factor in causing MEWDS, possibly by exposing otherwise isolated antigens. The anatomy in a highly myopic eye may make it challenging to diagnose MEWDS-associated fundus changes.
Keywords: MEWDS; high myopia; pathogenesis; autofluorescence; OCT